Civilisational change: markets and privatisation among indigenous peoples - Nathan, Dev; Kelkar, Govind
The paper deals with changes in the social and economic system of indigenous peoples upon integration into market systems. The change in production norms is not confined to elite accumulation but also results in a change at all levels, marking a civilisational change from a system based on stability to one based on accumulation. the new norms, however, come at the price of loss of guaranteed access to productive resources, the decline of traditional social welfare systems and the spread of commoditisation. Such a transition, however, need not be a surrender to laizzez-faire or neo-liberal policies, but can deal with negativities, including increasing masculine domination. New forms of community and continued non-market access to critical resources, like land and forests, would allow for a greater spread of the benefits. - Reproduced.
Keywords: Privatization; Civilization; Indigenous populations